Annual Plan 1966-67 Part II-Statements Government of Maharashtra - Planning Commission (Planning Commission, 1966)
Abstract statement of Plan Outlays on State Plan Schemes for the year 1966-67 Abstract statement of Plan Outlays on Centrally Sponsored Schemes for year 1966-67 List of Schemes included in the State Plan List of Schemes included in the Centrally Sponsored Programme Targets and achievements for selected programmes.
Government of Maharashtra Finance Department (Planning)